1993
DOI: 10.1111/j.1348-0421.1993.tb01691.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Response to Nontypable Haemophilus influenzae in Respiratory Infections

Abstract: Sputa from patients with respiratory infections by nontypable Haemophilus influenzae (H. influenzae) were investigated by electron microscopy. The cell wall of H. influenzae appeared wavy and nonwavy. In the cell wall the peptidoglycan layer was ill-defined. These patients had adequate IgG response in the serum against H. influenzae. However neither capsule nor fimbriae were found. Different stages of phagocytosis and destruction of the bacteria by polymorphonuclear neutrophils (PMN) were observed. PMNs were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…These studies clearly indicated that the receptor of H. influenzae resides in the sequence of gangliosides (6,9,10,22). Although several studies have shown that H. influenzae causing respiratory infections are mostly nontypable (1,11,12,22), till now, only one study was done to evaluate ganglioside interactions with NTHI (6). That study showed the receptor as a minor ganglioside.…”
mentioning
confidence: 99%
“…These studies clearly indicated that the receptor of H. influenzae resides in the sequence of gangliosides (6,9,10,22). Although several studies have shown that H. influenzae causing respiratory infections are mostly nontypable (1,11,12,22), till now, only one study was done to evaluate ganglioside interactions with NTHI (6). That study showed the receptor as a minor ganglioside.…”
mentioning
confidence: 99%